Assessment of Body Composition, Bone Density, and Biochemical Markers of a Natural Bodybuilder During Contest Preparation - Konstantinos Michailidis; Nikolaos Zaras; Dimitrios Balampanos; Alexandra Avloniti; Theodoros Stampoulis; Maria Protopapa; Dimitrios Pantazis; Nikolaos-Orestis Retzepis; Ilias Smilios; Athanasios Chatzinikolaou (Applied Sciences)
This case study aimed to evaluate the body composition and several biochemical markers during a 7-month pre-competition training period of a natural male bodybuilder. The athlete monitored his nutrition, training variables, and daily physical activity during the preparation phase. At the beginning (W31), in the middle (W18), and one week before the contest (W1), measurements included body composition via DEXA, testosterone and cortisol hormonal concentrations, and lipid, blood, and liver biochemical markers via an automated hematology analyzer. A gradual decrease in energy intake (−27.6%) and increased daily activity (169.0%) was found. Fat mass decreased from 17.9 kg (W31) to 13.1 kg (W18) and 4.2 kg (W1), while lean body mass decreased from 69.9 kg (W31) to 68.2 kg (W18) and 66.7 kg (W1). Bone density decreased linearly, and bone mass decreased from W31 to W1 by 1.7%. Testosterone decreased from 5.4 ng·mL−1 (W31) to 5.3 ng·mL−1 (W18) and 4.4 ng·mL−1 (W1), while cortisol increased from 21.3 μg·dL−1 (W31) to 20.3 μg·dL−1 (W18) and 24.4 μg·dL−1 (W1). In conclusion, a slow rate of weight loss and training with repetitions nearly to failure, combined with weekly monitoring of training and nutrition, may significantly improve body composition. However, hormone concentration and bone mass will experience mild negative effects.